LOCAL VS GLOBAL WOMEN’S REPRESENTATION IN NEWSPAPER ADVERTISING: A HISTORICAL STUDY OF LOCAL DAILY NEWSPAPERS (WASPADA, SINAR INDONESIA BARU AND ANALISA) IN MEDAN IN THE 1970s) - Lila Pelita Hati; Lestari Dara Cinta Utami Ginting (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This journal discusses the global discourse that appeared in local newspapers related to women’s representation. During the New Order era, especially since the 1970s, newspaper advertising experienced rapid growth. In the 1970s, there were three local daily newspapers in Medan; Waspada, Sinar Indonesia Baru, and Analisa. The three daily newspapers displayed various advertisements in their publications. Many advertisements use women to promote their products and services as a means of promotion. Women seemed to have their charm to attract market share. This study wants to explain how women’s representation in these local daily newspaper advertisements in Medan in the 1970s and how women became commodities in advertisements associated with global discourse, especially in terms of appearance. The authors applied the four stages of the historical method to conduct the research, namely heuristics, verification, interpretation, and historiography. The study results show that advertising producers often showcased pictures of beautiful and sexy women and even displayed vulgar words to attract consumers who did not represent local female figures.